Natural Characteristics and Human Activity Influence Turbidity and Ion Concentrations in Streams. (9th June 2021) - Scott, Erin E.; Haggard, Brian E.
Abstract: All 54 km of the West Fork of the White River (WFWR) were on Arkansas's 303(d) list of impaired waterbodies for turbidity, total dissolved solids (TDS), and sulfate for many years. This study identifies which river segments fail to meet applicable water quality standards (WQS) and investigates possible anthropogenic or natural sources of pollutants. We also evaluated a larger dataset of 119 sites in the Boston Mountains and Ozark Highlands ecoregions, compiled from the Arkansas Department of Environmental Quality online database. In the WFWR, water samples were collected once or twice a month at nine sites from June 2014 through June 2018. Median values for turbidity, TDS, sulfate, and chloride ranged from 1.8 to 10.8 NTU, 40.8 to 151.3 mg/L, 3.5 to 27.9 mg/L, and 3.2 to 5.5 mg/L, respectively, and generally increased from upstream to downstream (p < 0.05). Violations of the water quality standard for the parameters of interest varied by site, but generally occurred in the downstream portion of the WFWR, where land use, riparian soils, and underlying geology change. In the larger dataset, turbidity, TDS, sulfate, and chloride concentrations were all significantly greater in the Ozark Highlands than the Boston Mountains ecoregion (p < 0.05). Anthropogenic activities influence dissolved ion concentrations across these study sites, while geology and riparian soils may be important factors for differences in sulfate and turbidity.